The Implementatation of Curriculum based on CEFR in English Teaching - Linda Astrianingsih; Dwinalida, Khairunnisa (Prodi PBA Fakultas Tarbiyah dan Ilmu Keguruan UIN Saizu Purwokerto, 2024)
The research aimed to observe and describe the implementation of The Curriculum based on CEFR (Common European Framework for Languages) for English teaching conducted by English teachers in SD Al-Irsyad Al Islamiyyah 01 Purwokerto. A case study based on the qualitative method was chosen as the research design. The instruments for collecting data were interviews, observation and documentation. All the data were analyzed based on a qualitative approach, including data reduction, display data, conclusion drawing and verification. The result of the research shows the activity of English teaching implemented utterly appropriate to the principle of The Common European Framework of Reference for Languages (CEFR), such as comprehensive, transparent, coherent, supportive of lifelong learning, multidimensional, action-oriented, and supportive of student autonomy. Otherwise, some challenges that faced English teachers, such as time allotment, teaching media, using authentic material for listening activities, teaching grammar and intercultural competence. Therefore, the practice of this implementation needs more improvement to achieve the objective of the curriculum.